Calibration/Validation of Visible Infrared Imaging Radiometers and Applications - Changyong Cao (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In a new era of global awareness and globalization, what’s happening around the world in real-time such as hurricanes, volcanic eruption, fires, drought, pollution, and other environmental and climate challenges are becoming increasingly more important and affect people’s lives. To meet these challenges, Earth observations from a new generation of satellites have now become available giving us unprecedented capabilities to monitor and study our planet. With global coverage twice daily for the next several decades, the Visible Infrared Imaging Radiometers on polar orbiting satellites provide rich and publically available data sets for a large number of land, atmosphere, and ocean applications, including the monitoring of aerosols, cloud properties, radiation budget, sea surface temperature, ocean color, active fire, albedo, snow and ice, vegetation, land use/land cover, night-lights from human activities, and natural disasters. Calibration and validation of these satellite observations are essential to ensure the quality, accuracy, precision, and stability of the data for the applications. This book will review recent advances in satellite optical sensor calibration and validation methodologies, algorithms, and techniques. Example calibration and validation of environmental data products are also discussed. It aims to serve all professionals, researchers, students, scientists alike in academics, industries, government, and beyond.